Dual activity of PNGM-1 pinpoints the evolutionary origin of subclass B3 metallo-β-lactamases: a molecular and evolutionary study. Issue 1 (1st January 2019) - Lee, Jung Hun; Takahashi, Masayuki; Jeon, Jeong Ho; Kang, Lin-Woo; Seki, Mineaki; Park, Kwang Seung; Hong, Myoung-Ki; Park, Yoon Sik; Kim, Tae Yeong; Karim, Asad Mustafa; Lee, Jung-Hyun; Nashimoto, Masayuki; et al.
ABSTRACT: Resistance to β -lactams is one of the most serious problems associated with Gram-negative infections. β -Lactamases are able to hydrolyze β -lactams such as cephalosporins and/or carbapenems. Evolutionary origin of metallo- β -lactamases (MBLs), conferring critical antibiotic resistance threats, remains unknown. We discovered PNGM-1, the novel subclass B3 MBL, in deep-sea sediments that predate the antibiotic era. Here, our phylogenetic analysis suggests that PNGM-1 yields insights into the evolutionary origin of subclass B3 MBLs. We reveal the structural similarities between tRNase Zs and PNGM-1, and demonstrate that PNGM-1 has both MBL and tRNase Z activities, suggesting that PNGM-1 is thought to have evolved from a tRNase Z. We also show kinetic and structural comparisons between PNGM-1 and other proteins including subclass B3 MBLs and tRNase Zs. These comparisons revealed that the B3 MBL activity of PNGM-1 is a promiscuous activity and subclass B3 MBLs are thought to have evolved through PNGM-1 activity.